2020
DOI: 10.1093/cid/ciaa1166
|View full text |Cite
|
Sign up to set email alerts
|

Household Transmission of Severe Acute Respiratory Syndrome Coronavirus-2 in the United States

Abstract: Background Although many viral respiratory illnesses are transmitted within households, the evidence base for SARS-CoV-2 is nascent. We sought to characterize SARS-CoV-2 transmission within US households and estimate the household secondary infection rate (SIR) to inform strategies to reduce transmission. Methods We recruited laboratory-confirmed COVID-19 patients and their household contacts in Utah and Wisconsin during Marc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

18
133
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(161 citation statements)
references
References 28 publications
18
133
6
1
Order By: Relevance
“…In collaboration with state and local health departments and in the setting of public health emergency response, the U.S. Centers for Disease Control and Prevention (CDC) conducted a household transmission investigation during March-May 2020 in Milwaukee, Wisconsin, and Salt Lake City, Utah, metropolitan areas. Methods from the full investigation are available at Lewis et al 11 ; here, we describe a secondary analysis of the overall household transmission investigation focusing on details related to children in the households. In brief, we approached and enrolled a convenience sample of index case-patients with laboratory-confirmed SARSby guest on October 31, 2020 www.aappublications.org/news Downloaded from…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…In collaboration with state and local health departments and in the setting of public health emergency response, the U.S. Centers for Disease Control and Prevention (CDC) conducted a household transmission investigation during March-May 2020 in Milwaukee, Wisconsin, and Salt Lake City, Utah, metropolitan areas. Methods from the full investigation are available at Lewis et al 11 ; here, we describe a secondary analysis of the overall household transmission investigation focusing on details related to children in the households. In brief, we approached and enrolled a convenience sample of index case-patients with laboratory-confirmed SARSby guest on October 31, 2020 www.aappublications.org/news Downloaded from…”
Section: Study Populationmentioning
confidence: 99%
“…Among adult contacts, 74% were between 18-49 years, and 49 (41%) had an underlying medical condition. A full description of household characteristics and mitigation measures in the household is available at Lewis et al 11 Prepublication Release ©2020 American Academy of Pediatrics…”
Section: Study Populationmentioning
confidence: 99%
“…Some report lower attack rates in children compared with adults, 10,11 while others show no difference. [12][13][14][15] In a study of 58 United States households (58 index cases plus 188 household contacts), children and partners of index cases were more likely to be infected than other household members including siblings, parents and extended family members. 13 This suggests that children and adults may be similarly susceptible to infection, and that behavioural and environmental factors may underlie any difference in attack rate.…”
mentioning
confidence: 99%
“…In this issue of Pediatrics, Laws and colleagues add to this body of literature with a secondary analysis of a previously reported household contact study. 1 They describe infection rates, transmission dynamics, and symptom profiles in a cohort of US children with household SARS-CoV-2 exposure between March and May 2020 in Milwaukee and Salt Lake City. 2 The authors found that secondary infection rates in household contacts was similar in children (19/68 contacts; 28%) and adults (36/120 contacts; 30%).…”
mentioning
confidence: 99%